Radioactive ion beam opportunities at the new FRAISE facility of INFN-LNS - Martorana, N. S.; Cardella, G.; Guazzoni, C.; Pagano, E. V.; Russo, A. D.; Russotto, P.; Acosta, L.; Amato, A.; Calabretta, L.; Caruso, A.; Cavallaro, S.; Cosentino, L.; et al. (Frontiers in Physics, 2022)
At the Laboratori Nazionali del Sud of INFN (INFN-LNS) the construction of the new Radioactive Ion Beams (RIBs) facility FRAISE (FRAgment In-flight SEparator) has reached its ending phase. The facility will employ the in-flight technique by means of a primary beam fragmentation impinging on light Be or C targets. FRAISE will make use of light and medium mass primary beams having power up to ≈ 2-3 kW, leading to RIBs which intensities vary in the range of ≈ 10^3 pps up to ≈ 10^7 pps, for nuclei far and close from the stability valley, respectively. FRAISE aims at providing high-intensity and high-quality RIBs for nuclear physics experiments, also serving to interdisciplinary research areas, such as the medical physics. Critical aspects for high-quality beams are the tuning and the transport, representing time-consuming processes and requiring dedicated diagnostics and tagging devices measuring many features of RIBs. Some of these devices should be capable to operate in radioactively activated environments because of the expected ≈ 2 kW beam lost in the dipole after the production target. Due to their peculiar robustness to radioactive damage, Silicon Carbide (SiC) technology has been considered to make the array detectors needed. In this view, an R&D campaign has been started aiming at developing the FRAISE facility, the new diagnostics system, and a new tagging device, the latter of which will be useful for the CHIMERA multidetector beamline. In this paper, we will discuss the status and the perspectives of the facility with a focus on the RIBs opportunities.